2017
DOI: 10.5041/rmmj.10317
|View full text |Cite
|
Sign up to set email alerts
|

The Urology Residency Program in Israel—Results of a Residents Survey and Insights for the Future

Abstract: ObjectiveUrology practice has undergone several changes in recent years mainly related to novel technologies introduced. We aimed to get the residents’ perspective on the current residency program in Israel and propose changes in it.MethodsA web-based survey was distributed among urology residents.Results61 residents completed the survey out of 95 to whom it was sent (64% compliance). A total of 30% replied that the 9 months of mandatory general surgery rotation contributed to their training, 48% replied it sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In terms of experience in laparoscopy during residency, there is a generalized feeling amongst residents that training is inadequate, with most residents having a low degree of confidence in independently performing laparoscopic procedures by the end of residency [4,5,6,7,8,9,10,11]. The only exception is the study by Preston et al [10] where 67% of Canadian responders considered their experience to be good or extensive.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…In terms of experience in laparoscopy during residency, there is a generalized feeling amongst residents that training is inadequate, with most residents having a low degree of confidence in independently performing laparoscopic procedures by the end of residency [4,5,6,7,8,9,10,11]. The only exception is the study by Preston et al [10] where 67% of Canadian responders considered their experience to be good or extensive.…”
Section: Discussionmentioning
confidence: 87%
“…The studies analyzed reported considerable differences in terms of exposure to laparoscopy during residency programs [4,5,6,7,8,9,10,11]. The article by Furriel et al [9] reported that 25% of respondents from European Union Urology residency programs do not have access to laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations